O princípio constitucional da segurança jurídica na jurisprudência do Supremo Tribunal Federal : a tutela de expectativas não abrangidas pela proteção aos direitos adquiridos - Nascimento, Leandro Maciel do (2015)
The demand for stability and security in legal relations is a constant search in society. It is inherent in the legal system the tension of having to upgrade their standards and at the same time preserving interests and expectations generated from previously established legal relations. The Law balances between innovation and conservation. This tension became more pronounced during the Twentieth Century, when contemporary society became known as risk society or postmodern society. The result was the constant search for diminishing the effects of so much instability and the necessary return of concerns about legal certainty, as constitutional command. In Brazilian Law, there are three main mechanisms of realization of legal certainty: the protection of acquired rights, the preservation of the effects of legitimate confidence and the stabilization of fact situations consolidated over time. The protection of acquired rights is the most traditional mechanism in Brazilian law, but not in comparative law. However, this protection has limits, and in many situations it is not enough to preserve legitimate expectations. For these cases, the brazilian Supreme Court recognizes other instruments: on the one hand, confidence protection and on the other, the preservation of consolidated fact situations. The protection of confidence requires four conditions: legitimate basis, situation of confidence, concrete exercise of such confidence and its frustration because of the Government's behavior change. Finally, the brazilian Supreme Court recognizes the preservation of interest and expectation not covered by the previous protections, by maintaining, in exceptional conditions, situations that although irregular in their origin, have become irreversible or difficult to reverse.